Description Of Neonatorum Asfixia Events In H. A. Sulthan Daeng Radja Hospital Bulukumba District - Sari, Iramaya; Marwidah (Jurnal Life Birth, 2017)
Newborns are individuals who are growing up and have just experienced birth trauma and must be able to make adjustments from intrauterine to extrauterine life. The main causes of death in newborns in the world include LBW 29%, sepsis, and pneumonia 25%, and asphyxia 23%. Asphyxia occupies the third cause of infant death in the world in the early period of life. Asphyxia is a condition in which a newborn cannot breathe spontaneously and regularly after birth. One of the causes of asphyxia is maternal gestational age <37 and> 42 weeks. The purpose of this study was to determine the description of the incidence of asphyxia neonatorum in H. Andi Sulthan Daeng Radja District Hospital, Bulukumba Regency. The research design used was a descriptive study, which was carried out in August at H. Andi Sulthan Daeng Radja Hospital in Bulukumba Regency. The total population of all newborns is 1,678. The sampling technique used is Total Sampling for infants with asphyxia as many as 107, Simple Random Sampling by lottery for infants who are not asphyxia as many as 107. Data is collected through a register book then the data is processed by editing, coding, tabulating, and analyzed using the SPSS Program. the study showed that the majority of infants with asphyxia were <37 weeks of gestation and> 42 weeks of pregnancy (86.4%), while the low risk of not having asphyxia was 87 (81.3%). high-risk pregnancies are 86 (80.4%). For this reason, health workers are expected to always pay attention to the condition of the mother and baby by increasing their skills in handling neonatal emergencies by detecting the health of mothers and newborns early.